ISLAMIC EDUCATION VALUES IN THE NUSSA ANIMATION SERIES EPISODE TOLERANCE - Ramadhani, Sari; Hasballah Thaib, Zamakhsyari bin; Aqsho, Muhammad (Universitas Dharmawangsa, 2024)
The aim of this research is to determine: (1) The values of Islamic education in the animated series Nussa episode of tolerance, (2) The relevance of the values of Islamic education in the animated series Nussa episode of tolerance with the Quran, and (3) Correlation the values of Islamic education in the animated series Nussa, tolerance episode with the challenges of today's Islamic education. This research uses qualitative research methods in the form of library research, where the majority of this research is analyzing and reviewing books and other literature as references related to the theme being researched. The results obtained from this research show that: (1) There are three values of Islamic education in the animated series Nussa episode tolerance, namely i'tiqodiyah values, amaliyah values, and khuluqiyah values. (2) There is relevance of Islamic education values in the Nussa animation series, tolerance episode with the Quran, such as i'tiqodiyah values which are relevant to (QS. An-Nisa' [4]: 136), relevant amaliyah values with (QS. Al-'Ankabut [29]: 46), and (QS. Al-Mumlahanah [60]: 8) which are relevant to the value of khuluqiyah. (3) It was found that there was a correlation between the values of Islamic education in the animated series Nussa episode of tolerance and the challenges of Islamic education today, namely the use of advances in science and technology, the good morals displayed that can be an example so that moral decadence does not occur, and the existence of educational democracy. An-Nisa' [4]: 136), amaliyah values which are relevant to (QS. Al-'Ankabut [29]: 46), and (QS. Al-Mumlahanah [60]: 8) which are relevant to khuluqiyah values. (3) It was found that there was a correlation between the values of Islamic education in the animated series Nussa episode of tolerance and the challenges of Islamic education today, namely the use of advances in science and technology, the good morals displayed that can be an example so that moral decadence does not occur, and the existence of educational democracy. An-Nisa' [4]: 136), amaliyah values which are relevant to (QS. Al-'Ankabut [29]: 46), and (QS. Al-Mumlahanah [60]: 8) which are relevant to khuluqiyah values. (3) It was found that there was a correlation between the values of Islamic education in the animated series Nussa episode of tolerance and the challenges of Islamic education today, namely the use of advances in science and technology, the good morals displayed that can be an example so that moral decadence does not occur, and the existence of educational democracy.